RELATION OF INCIDENT NURSING BOTTLE CARIES 3-5 YEARS OLD CHILDREN WITH MOTHER’S BEHAVIOR WHO GIVE BOTTLE FEEDING OF MILK WITH - Berlian Pratiwi; Febrian Febrian (Faculty of Dentistry Universitas Andalas, 2013)
The study aim to find the relation of mother’s behavior who giving bottle feeding with Nursing Bottle Caries in 3-5 years old children. The design of this study was cross-sectional analytic with subjects were 78 children from 3 to 5 years old with her mother in Padang Timur. Data collection was done by dental examination on children and interviewing with their mother. The result showed that 88,64 percent children 3 to 5 years old was got Nursing Bottle Caries. The Chi-Square test showed there is no relation between mothers’s knowledge with Nursing Bottle Caries (p>0,05) and there is relation between mother’s attitude and action with Nursing Bottle Caries (p<0,05).